Banco de dados do projeto plantas aromáticas do Estado do Pará. - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1994)
Every year thousands of chemical compounds are commercialized aiming to supply the pharmaceutical, cosmetic, and perfume industries with the purpose of promoting more efficient and accessible products to the population. However, due to the uncontrolled extractive exploitation and with the scarcity of raw materials increasing every year, it becomes necessary to replant, as well as to find new sources of production. In this sense, new research is necessary. However, in order to study the vast aromatic flora of the state of Pará, a group of people has been developing a project that aims to triage the odoriferous flora and whose objective is to assemble a database of the species found in our region, identifying the economic potentials. Several botanical species were collected, in different locations in the interior of Pará State, as well as species located at the Emílio Goeldi Zoobotanic Park. All the collected material was transported to the Research Campus of the Emílio Goeldi Museum, where after seven days of drying it was submitted to essential oil extraction by steam dragging using a modified "clevenger" with condensed water coobation. The oils obtained were analyzed in a gas chromatograph coupled to a mass spectrometer, and then all the results obtained were stored in a database. The present work reports data such as: place of collection, percentage of essential oil, part of the plant used and the chemical components of the species studied.
Database of the project aromatic plants of the State of Pará.
Keywords: Plantas aromáticas; Pará; CNPQ::CIENCIAS BIOLOGICAS::ECOLOGIA